Transformation Of The University Curriculum: An Evaluation Study Of The Islamic Religious Education Curriculum With The Provus Discrepancies Model - Bobi Erno Rusadi (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This study evaluates the curriculum of the Islamic Education (PAI) Program at UIN Syarif Hidayatullah Jakarta using the Provus Discrepancy Model to identify gaps between curriculum design and implementation. The evaluation focuses on three components: needs analysis, curriculum design, and implementation. Data were collected through document analysis, observations, and in-depth interviews with stakeholders, and analyzed qualitatively. Findings reveal significant discrepancies. While the graduate profile includes prospective Islamic education teachers, researchers, and counselors, tracer studies show that 86% of graduates become teachers, with limited outcomes in the other roles. Curriculum revision is irregular and not aligned with the standard five-year cycle, leading to misalignment with job market demands. Excessive learning outcomes (CPLs) complicate assessment, and credit loads often exceed regulatory limits. In implementation, teaching remains predominantly teacher-centered, with limited use of Student-Centered Learning (SCL) and minimal emphasis on project-based or socio-emotional assessment. The study recommends regular, stakeholder-driven curriculum updates, reinforcement of research and counseling competencies, adoption of Outcome-Based Education (OBE), and greater integration of technology. A balanced application of cognitive, affective, and psychomotor assessments through SCL methods is essential to achieve a holistic graduate profile.Keywords: Curriculum Evaluation, Islamic Religious Education, Provus Discretionary Model,